A method of construction of a steel fibre dispersed non-explosive concrete
Patent Information
- Application Number
- CN202511518879.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-23
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-10-23
AI Technical Summary
[0004]为了克服现有技术的上述缺陷,本发明的实施例提供一种钢纤维分散制备的不发火混凝土施工方法,解决了现有技术中矿井不发火混凝土超细钢纤分散差、早强不足、环保适配性低的问题
[0025] 1. This invention achieves precise dispersion of ultrafine steel fibers, ensuring uniform and stable non-sparking performance: Through an integrated composite carrier design of "corn stalk ash-based porous carbon encapsulation + soluble salt crystal anchoring," the agglomeration of ultrafine steel fibers during transportation and feeding is avoided from the source; coupled with a one-stop dispersion device driven by mine compressed air, through the three-stage synergistic effect of airflow crushing, stretching and peeling, and electrostatic elimination, the industry pain point of ultrafine steel fibers being prone to electrostatic agglomeration due to their large specific surface area is effectively solved, achieving uniform dispersion of steel fibers in the concrete matrix, ensuring consistent impact and spark resistance performance in all areas of the concrete, and meeting the core requirement of "no local safety hazards" for non-sparking concrete in underground mines.
Smart Images

Figure CN121225908B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of concrete construction technology, and particularly relates to a method for constructing non-sparking concrete prepared by steel fiber dispersion. Background Technology
[0002] In underground mining engineering, non-sparking concrete is a core protective material to mitigate safety risks caused by impact and friction. Current technologies typically use ordinary Portland cement as a binder, combined with inert aggregates such as quartz sand and limestone crushed stone, and incorporate steel fibers to enhance impact resistance. Construction often employs concrete spraying machines, utilizing the mine's existing compressed air system for concrete delivery. In some scenarios, early-strength agents are added to shorten setting time. Curing primarily involves covering with insulating blankets and regularly sprinkling water to maintain humidity. To reduce the risk of steel fiber corrosion, the water-cement ratio is specifically controlled, or rust-resistant steel fibers are selected. This overall technology has been successfully applied in conventional underground mining construction scenarios.
[0003] However, existing non-sparking concrete technology for underground mines struggles to meet the demands for efficient, environmentally friendly, and long-term safe construction. Firstly, for ultra-fine steel fibers with a diameter ≤0.12mm, current technologies rely on mechanical mixing, failing to address the issue of electrostatic fiber agglomeration, resulting in uneven impact resistance and sparking performance of the concrete. Secondly, early-strength agents are mostly added directly, with limited hydration-promoting effects at low temperatures of 10-15℃, making them unsuitable for rapid underground support requirements. Thirdly, the technology does not integrate solid waste resource utilization, relying primarily on expensive synthetic materials, and traditional water-spraying curing is difficult to implement in water-scarce and confined underground spaces. Fourthly, there is a lack of methods to control the alkalinity of the concrete liquid phase, leading to easy corrosion of steel fibers during long-term service. Furthermore, some construction equipment requires external power, resulting in poor compatibility with mine power restrictions and confined space environments, making it difficult to balance construction convenience with structural durability. Summary of the Invention
[0004] In order to overcome the above-mentioned defects of the prior art, the embodiments of the present invention provide a construction method for non-sparking concrete prepared by steel fiber dispersion, which solves the problems of poor dispersion of ultrafine steel fibers, insufficient early strength and low environmental compatibility of non-sparking concrete in mines in the prior art.
[0005] To achieve the above objectives, the present invention provides the following technical solution:
[0006] A method for constructing non-sparking concrete prepared by steel fiber dispersion includes the following steps:
[0007] S1: Ground prefabrication of integrated composite carrier involves mixing corn stalk ash, soluble salt, and ultrafine steel fibers in a specific ratio to meet the non-sparking properties of concrete, the dispersibility of ultrafine steel fibers, and the requirements for low-temperature early strength in underground mining. The mixture is then kneaded, carbonized in an inert atmosphere, crushed, and sieved to obtain a spherical integrated composite carrier. The soluble salt functions as both a pore-forming agent and an early strength reserve during the carbonization process. The corn stalk ash forms a porous carbon matrix after carbonization, and the ultrafine steel fibers are fixed through "encapsulation of the porous carbon matrix + crystal anchoring of soluble salt".
[0008] S2: Underground dispersion and mixing. The integrated composite carrier obtained in step S1 is put into the hopper of the mine concrete spraying machine at a ratio of 0.8% to 1.5% of the concrete volume. Relying on the airflow provided by the existing compressed air system in the mine, the carrier is driven into a one-stop dispersion device installed on the feed pipe of the spraying machine. The carrier crushing, fiber stretching and peeling, fiber static elimination and closed-loop control of fiber concentration are completed in sequence. Then it is mixed with dry concrete and underground water to achieve simultaneous dissolution of soluble salts and uniform dispersion of ultrafine steel fibers.
[0009] S3: Underground pouring and curing. The steel fiber dispersed concrete obtained in step S2 is applied to the surface of the mine roadway or chamber using a wet spraying process to form a spray layer with a thickness of 50-100mm. Internal curing is achieved through the water retention effect of the porous carbon matrix. Construction is completed after curing for 28 days.
[0010] The one-stop dispersion device is a series three-stage functional compartment structure. Each compartment is sealed and connected by an airflow channel. Along the airflow direction, it consists of a first-stage crushing compartment for crushing the carrier, a second-stage stretching compartment for stripping steel fibers, and a third-stage regulating compartment for controlling fiber concentration. The entire process relies solely on mine compressed air for power, without any additional external power source.
[0011] Through the above steps, the dispersion variation coefficient of ultrafine steel fibers in concrete is ≤10%, and the impact ignition temperature of concrete is ≤220℃, meeting the environmental protection and safety construction requirements of underground mines.
[0012] Preferably, in step S1, the mass ratio of corn stalk ash to soluble salt is 3:1, the amount of ultrafine steel fiber added is 20% of the total mass of corn stalk ash and soluble salt; the diameter of the ultrafine steel fiber is 0.08-0.12 mm and the length is 2-3 mm; the soluble salt is anhydrous sodium sulfate.
[0013] Preferably, the specific prefabrication process in step S1 is as follows:
[0014] S11: Corn stalk ash, anhydrous sodium sulfate, and ultrafine steel fiber are put into a twin-screw mixer and mixed for 5 minutes at 80°C and 300 r / min to obtain a mixture.
[0015] S12: The mixture is fed into a carbonization furnace, N2 protective gas is introduced, and the temperature is raised to 800℃ at a heating rate of 5℃ / min. The temperature is held for 2 hours for carbonization treatment, and the block carbonized material is obtained after natural cooling.
[0016] S13: The blocky carbonized material is crushed and screened by jaw crusher to obtain a spherical integrated composite carrier with a particle size of 8-10mm and a compressive strength of ≥3MPa. After being sealed and packaged, it is transported to the underground silo for storage.
[0017] Preferably, in step S2, the compressed air pressure of the mine compressed air system is 0.4-0.6 MPa; the integrated composite carrier is added to the shotcrete machine hopper at a rate of 1.2% of the concrete volume.
[0018] Preferably, the primary crushing chamber of the one-stop dispersion device is equipped with a supersonic nozzle, the outlet velocity of which is 350-400 m / s, for crushing the spherical integrated composite carrier into particles of 5-8 mm; the secondary stretching chamber is a tapered flow channel structure with an inlet diameter of 120 mm and an outlet diameter of 60 mm, and the outlet velocity of the airflow after acceleration through the flow channel is 18-22 m / s, for stretching and peeling ultrafine steel fibers from the carrier particles.
[0019] Preferably, the three-stage control chamber of the one-stop dispersion device integrates an ion bar and a laser density sensor; the ion bar has a wind speed of 4-5 m / s and is used to reduce the electrostatic voltage on the surface of the ultrafine steel fiber from 5000V to ≤80V; the laser density sensor has a monitoring accuracy of ±2%, and when the fiber concentration fluctuation is detected to be >5%, the opening of the compressed air valve is automatically adjusted. Through the adjustment logic that every 10% increase or decrease in the opening of the compressed air valve corresponds to a synchronous increase or decrease of 0.02MPa in the compressed air pressure, the compressed air pressure fluctuation is controlled within the range of ±0.05MPa.
[0020] Preferably, in step S2, 5% antifreeze is added to the dry concrete; the amount of water added from the well is sufficient to meet the water-cement ratio of 0.45 for the concrete; the mixing time is 3-4 minutes, during which anhydrous sodium sulfate is completely dissolved, releasing Na⁺ ions to promote cement hydration.
[0021] Preferably, in step S3, the spraying pressure of the wet spraying process is 0.3-0.4 MPa; the thickness of the sprayed layer is 50-80 mm, which is suitable for the construction requirements of thin sprayed layers in underground mines.
[0022] Preferably, the curing process in step S3 is as follows: after the spray layer is formed, cover it with an insulation blanket to ensure that the curing environment temperature is ≥5℃. Internal curing is achieved by utilizing the microporous water storage function of the porous carbon matrix in the integrated composite carrier. The curing age is 28 days. The porosity of the porous carbon matrix is 65% to 70%, and the surface contains 20% carboxyl and phenolic hydroxyl functional groups, which can adsorb calcium hydroxide produced by cement hydration and reduce the pH value of the concrete liquid phase to 12.7-12.9.
[0023] Preferably, after construction, the dispersion variation coefficient of ultrafine steel fibers in concrete is ≤6%, which is achieved by the synergistic effect of airflow stretching and electrostatic elimination of the one-stop dispersion device; the 1-day compressive strength of concrete is ≥12.5MPa, which is achieved by the release of Na⁺ ions from anhydrous sodium sulfate to accelerate cement hydration; the 28-day strength retention rate is ≥95%, which is achieved by the internal curing function of the porous carbon matrix; the impact ignition temperature is ≤200℃, which is achieved by the absorption of impact energy by the inert structure of porous carbon; and the annual corrosion rate of ultrafine steel fibers is <2%, which is achieved by the adsorption of calcium hydroxide by porous carbon to reduce the pH value of the concrete liquid phase to 12.7-12.9.
[0024] The technical effects and advantages of the non-sparking concrete construction method prepared by steel fiber dispersion according to the present invention are as follows:
[0025] 1. This invention achieves precise dispersion of ultrafine steel fibers, ensuring uniform and stable non-sparking performance: Through an integrated composite carrier design of "corn stalk ash-based porous carbon encapsulation + soluble salt crystal anchoring," the agglomeration of ultrafine steel fibers during transportation and feeding is avoided from the source; coupled with a one-stop dispersion device driven by mine compressed air, through the three-stage synergistic effect of airflow crushing, stretching and peeling, and electrostatic elimination, the industry pain point of ultrafine steel fibers being prone to electrostatic agglomeration due to their large specific surface area is effectively solved, achieving uniform dispersion of steel fibers in the concrete matrix, ensuring consistent impact and spark resistance performance in all areas of the concrete, and meeting the core requirement of "no local safety hazards" for non-sparking concrete in underground mines.
[0026] 2. This invention is adapted to the low-temperature environment of mines and improves the early strength performance of concrete: the soluble salts in the composite carrier, such as anhydrous sodium sulfate, also function as an "early strength reserve". During the underground mixing process, they dissolve with the gushing water, and the released ions can accelerate the cement hydration reaction, significantly improving the early strength of concrete in the low-temperature environment of 10-15℃. This solves the problem of slow setting and low support efficiency of traditional mine concrete due to low temperature, and ensures the progress of underground construction and early structural stability.
[0027] 3. This invention promotes the resource utilization of solid waste, combining environmental protection and economic efficiency: using corn stalk ash, an agricultural waste, as raw material to prepare a porous carbon matrix, it transforms low-value solid waste into a core carrier with multiple functions such as "fiber fixation, alkalinity regulation, and internal maintenance," significantly improving the utilization rate of straw ash and reducing pollution from solid waste stockpiling; at the same time, it eliminates the need to purchase additional high-priced synthetic carriers, and the dispersion device relies on the existing compressed air system in the mine, requiring no external power supply or large equipment, significantly reducing construction costs and energy consumption, and meeting the industrial demand for both environmental protection and economic efficiency under the "dual carbon" background.
[0028] 4. This invention enhances the durability of concrete and extends the service life of underground structures: The porous carbon matrix has high porosity and abundant surface functional groups. On the one hand, it can adsorb calcium hydroxide produced by cement hydration, reduce the alkalinity of the concrete liquid phase, inhibit the corrosion of ultrafine steel fibers, and avoid the degradation of concrete structural performance caused by fiber corrosion. On the other hand, its microporous structure can store water, realize internal curing of concrete, solve the problem of water shortage in underground mines and the difficulty in implementing traditional water spraying curing, ensure the long-term strength retention rate of concrete, and extend the service life of underground roadways, chambers and other structures.
[0029] 5. This invention is highly adaptable to mine construction scenarios, improving construction convenience and safety: The entire construction process makes full use of existing mine conditions—using underground water inflow instead of external water production, and using a compressed air system to drive the dispersion device, eliminating the need for additional power supply and large equipment. The modular design of the device can be adapted to transportation and installation in narrow underground spaces. At the same time, the entire process is free of open flames and additional electrical risks, and the concrete has excellent impact resistance and corrosion resistance. It ensures the safety of underground operations in the mine from the construction process to the entire life cycle of structural use, solving the pain points of traditional concrete construction methods such as "difficult equipment entry and high safety risks". Attached Figure Description
[0030] Figure 1 This is a schematic diagram of the process flow for a non-sparking concrete construction method based on steel fiber dispersion proposed in this invention. Detailed Implementation
[0031] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0032] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitation, an element defined by the phrase "comprising..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0033] General preparation conditions
[0034] Raw material specifications: Corn stalk ash: SiO2 55%, Al2O3 20%, 80-mesh sieve residue ≤5%;
[0035] Soluble salts: anhydrous sodium sulfate (purity ≥99%), sodium nitrate;
[0036] Ultrafine steel fibers: diameter 0.08~0.12mm, length 2~3mm, tensile strength ≥3800MPa;
[0037] Dry concrete mix: P-O42.5 cement, quartz sand with a fineness modulus of 2.6, and crushed stone of 5-10mm, in a mass ratio of 1:1.5:2;
[0038] Antifreeze agent: Sodium nitrite compound admixture dosage 5%, based on cement weight;
[0039] Downhole water inflow: pH 7.2-7.5, suspended solids ≤50mg / L.
[0040] Core equipment:
[0041] Twin-screw mixer SHJ-35, carbonization furnace GWL-1200, jaw crusher PE-60×100;
[0042] A self-made, one-stop dispersion device, comprising three functional chambers: a first-stage supersonic nozzle, a second-stage tapered flow channel, and a third-stage ion air bar + laser sensor;
[0043] The PZ-5 concrete spraying machine features a laser density sensor with an accuracy of ±2% and a pressure sensor with an accuracy of ±0.01MPa.
[0044] Example 1
[0045] refer to Figure 1 This embodiment provides a construction method for non-sparking concrete prepared by steel fiber dispersion, for the implementation of a benchmark scheme. The specific implementation includes:
[0046] Purpose of implementation:
[0047] Verify the feasibility of the whole process solution of "integrated composite carrier + one-stop dispersion device + internal curing", and focus on supporting the implementation of technical features such as "0.8% to 1.5% volume ratio", "three-level functional compartment structure", "28-day curing period" and "specific prefabrication steps of integrated composite carrier".
[0048] Implementation steps:
[0049] S1: Ground prefabrication of integrated composite carrier:
[0050] Mix corn stalk ash and anhydrous sodium sulfate in a mass ratio of 3:1, and add 20% of the total mass of ultrafine steel fibers with a diameter of 0.10 mm and a length of 2.5 mm.
[0051] The specific prefabrication process is as follows:
[0052] S11: The corn stalk ash, anhydrous sodium sulfate and ultrafine steel fiber are put into a twin-screw mixer and mixed at 80°C and 300r / min for 5min to obtain a mixture.
[0053] S12: The mixture is fed into a carbonization furnace, N2 protective gas is introduced, the temperature is raised to 800℃ at a heating rate of 5℃ / min, and the temperature is held for 2 hours for carbonization treatment. After natural cooling, blocky carbonized material is obtained.
[0054] S13: The blocky carbides are crushed and screened by jaw crusher to obtain spherical integrated composite carriers with a particle size of 8-10 mm and a compressive strength of 3.2 MPa ≥ 3 MPa. After being sealed and packaged, they are transported to the underground silo for storage.
[0055] S2: Downhole dispersion and mixing:
[0056] The above-mentioned spherical integrated composite carrier is added at 1.2% of the concrete volume, and the compressed air pressure of the mine compressed air system is 0.5MPa;
[0057] The carrier enters the one-stop dispersion device along with the compressed air flow:
[0058] Primary crushing chamber: Supersonic nozzle outlet wind speed in the range of 380m / s to 350-400m / s, crushing spherical carriers into particles of 5-8mm;
[0059] Secondary stretching chamber: It adopts a gradually narrowing flow channel structure with an inlet diameter of 120mm and an outlet diameter of 60mm. After the airflow is accelerated, the outlet wind speed is in the range of 18 to 22m / s, which stretches and peels the ultra-fine steel fibers from the carrier particles.
[0060] Three-stage control chamber: The ion wind bar wind speed is in the range of 4.5m / s to 4 to 5m / s, reducing the electrostatic voltage on the surface of the ultrafine steel fiber to 70V≤80V; the laser density sensor monitors the fiber concentration in real time with a monitoring accuracy of ±2%, and when the concentration fluctuation is ≤5%, the compressed air pressure fluctuation is controlled within ±0.03MPa≤±0.05MPa;
[0061] Add 5% antifreeze to the dry concrete material in the hopper of the shotcrete machine, add well water at a water-cement ratio of 0.45, and mix with the dispersed steel fibers for 3.5 to 3-4 minutes. During the mixing process, the anhydrous sodium sulfate should be completely dissolved.
[0062] S3: Underground pouring and curing:
[0063] Using a wet spraying process with a spraying pressure ranging from 0.35MPa to 0.4MPa, steel fiber dispersed concrete is applied to the surface of the mine roadway to form a 60mm thick spray layer with a range of 50-80mm.
[0064] After the spray layer is formed, cover it with an insulation blanket to ensure the curing environment temperature is 5-8℃ or higher. Utilize the microporous water storage function of the porous carbon matrix in the integrated composite carrier to achieve an internal curing porous carbon matrix porosity of 68% to 70%, and cure for 28 days.
[0065] During the curing process, the carboxyl and phenolic hydroxyl functional groups on the surface of the porous carbon matrix adsorb Ca(OH)2 produced by cement hydration, causing the pH value of the concrete liquid phase to drop to the range of 12.8-12.7-12.9.
[0066] Implementation results:
[0067] The dispersion variation coefficient of ultrafine steel fibers in concrete is 5.2% ≤ 6%;
[0068] The 1-day compressive strength of concrete is 13.2 MPa ≥ 12.5 MPa, and the 28-day strength retention rate is 96.5% ≥ 95%.
[0069] The impact ignition temperature of concrete is 195℃≤200℃;
[0070] The annual corrosion rate of ultrafine steel fibers is 1.8% < 2%.
[0071] Example 2
[0072] This embodiment provides a method for constructing non-sparking concrete prepared by steel fiber dispersion, which is used to adjust the amount of steel fiber added. The specific implementation includes:
[0073] Purpose of implementation:
[0074] The rationality of adding 20% of the total mass of steel fiber was verified, and the effect of changes in the amount added was tested on the dispersibility.
[0075] The implementation steps are the same as in Example 1, except that the amount of fiber added in S1 is changed.
[0076] S1: The amount of steel fiber added is 15% of the total mass of corn stalk ash and soluble salt; the rest is the same as in Example 1.
[0077] S2, S3: Same as in Example 1.
[0078] Implementation results:
[0079] The dispersion coefficient of variation of 4.8% is better than the benchmark, due to the reduced fiber content and lower risk of agglomeration;
[0080] The 1-day compressive strength of 12.8 MPa is slightly lower than the benchmark due to the weakened fiber reinforcement effect;
[0081] The impact ignition temperature is 198℃, and the annual corrosion rate is 1.7%, which is close to the benchmark.
[0082] Conclusion: A 20% addition of support is the optimal value that balances strength and dispersibility.
[0083] Example 3
[0084] This embodiment provides a construction method for non-sparking concrete prepared by steel fiber dispersion, which is used to adjust the compressed air pressure. The specific implementation includes:
[0085] Purpose of implementation:
[0086] Verify the effectiveness of the compressed air pressure of 0.4-0.6MPa and pressure fluctuation control technology.
[0087] The implementation steps only change the compressed air pressure of S2; the rest are the same as in Example 1.
[0088] S2: Compressed air pressure 0.4MPa, the valve opening adjustment logic of the three-stage control chamber remains unchanged, each 10% corresponds to 0.02MPa;
[0089] S1, S3: Same as in Example 1.
[0090] Implementation results:
[0091] The dispersion coefficient of variation of 5.8% is slightly higher than the baseline, due to insufficient tensile strength caused by reduced pressure;
[0092] Pressure fluctuation ±0.04MPa;
[0093] 1-day compressive strength 12.5 MPa, impact ignition temperature 200℃.
[0094] Conclusion: The effective pressure range is 0.4-0.6 MPa, and the adjustment logic is feasible.
[0095] Example 4
[0096] This embodiment provides a construction method for non-sparking concrete prepared by steel fiber dispersion, used for adjusting the carbonization temperature. Specific implementation details include:
[0097] Purpose of implementation:
[0098] The effect of carbonization temperature of 800℃ on the properties of porous carbon matrix was verified, with a supporting porosity of 65% to 70%.
[0099] The implementation steps are the same as in Example 1, except that the carbonization temperature of S1 is changed.
[0100] S1: Carbonization temperature 750℃;
[0101] S2, S3: Same as in Example 1.
[0102] Implementation results:
[0103] The carrier compressive strength is 3.0 MPa;
[0104] The 28-day strength retention rate of 95.5% was slightly lower than the benchmark, which was due to the reduced porosity leading to a weakened internal curing effect.
[0105] The pH value of the liquid phase is 12.9;
[0106] The annual corrosion rate of 2.0% is close to the benchmark.
[0107] Conclusion: Carbonization at 800℃ is the optimal parameter, and the porosity range is reasonable.
[0108] Example 5
[0109] This embodiment provides a method for constructing non-sparking concrete prepared by steel fiber dispersion, which is used to adjust the types of soluble salts. The specific implementation includes:
[0110] Purpose of implementation:
[0111] Verify the suitability of anhydrous sodium sulfate as the soluble salt and test the substitution effects of other soluble salts.
[0112] The implementation steps are the same as in Example 1, except that the type of soluble salt in S1 is changed.
[0113] S1: Soluble salt is replaced with sodium nitrate in the same mass ratio;
[0114] S2, S3: Same as in Example 1.
[0115] Implementation results:
[0116] The 1-day compressive strength of 13.0 MPa is close to the benchmark, proving that the early strength function of soluble salt has universality;
[0117] The coefficient of variation is 5.3%, and the impact ignition temperature is 196℃, both of which meet the requirements.
[0118] The annual corrosion rate of 1.8% is consistent with the benchmark.
[0119] Conclusion: The choice of supporting soluble salts is flexible, with anhydrous sodium sulfate being a preferred but not the only option.
[0120] Comparative Example 1
[0121] This comparative example provides a traditional technical solution, the specific contents of which include:
[0122] Purpose of implementation:
[0123] Verify the necessity of integrated composite carrier, one-stop dispersion device, and porous carbon internal curing.
[0124] Implementation steps:
[0125] S1-free composite carrier prefabrication: directly mechanically mix ultrafine steel fibers of the same specification with dry concrete materials;
[0126] One-stop dispersion unit without S2: It adopts conventional mechanical stirring and dispersion, and compressed air is only used for spraying;
[0127] S3-free porous carbon internal curing: Traditional water spraying curing is difficult to implement in downhole operations.
[0128] Implementation results:
[0129] The coefficient of variation was 18.5%.
[0130] The 1-day compressive strength of 8.2 MPa is only 60% of that of the example, demonstrating the importance of the early strength function of soluble salts;
[0131] The 28-day strength retention rate was 82.3%, and the impact ignition temperature of 260℃ did not meet the safety requirements, proving the role of porous carbon.
[0132] The annual corrosion rate of 5.6% is three times that of the example, demonstrating the necessity of pH control.
[0133] Comparing Examples 1-5 with Comparative Example 1, the comparison of Examples 1-5 with Comparative Example 1 is summarized as follows:
[0134] Examples 1-5 are based on the core solution of the present invention, namely "integrated composite carrier prefabrication + one-stop compressed air dispersion + multi-functional synergy of porous carbon". All of them use corn stalk ash-based porous carbon-soluble salt composite carrier to fix ultrafine steel fibers, rely on mine compressed air to drive a three-stage dispersion device, and combine porous carbon internal curing. Comparative Example 1 is a conventional construction method, which directly mechanically stirs ultrafine steel fibers without composite carrier, special dispersion device and porous carbon synergy. The two are significantly different in core performance and scenario adaptability.
[0135] Regarding the dispersion of steel fibers, the coefficient of variation of steel fiber dispersion in Examples 1-5 is ≤5.8%, with Example 1 having the lowest coefficient of variation at 5.2%, which is only 1 / 3 of the 18.5% of the comparative example. The core reason is that the examples avoid transport agglomeration through "porous carbon matrix encapsulation + soluble salt crystal anchoring". Then, the dispersion is achieved by airflow crushing at 350-400m / s supersonic nozzle, stretching at 18-22m / s airflow shearing and electrostatic elimination voltage ≤80V in a one-stop dispersion device, thus achieving single-fiber-level dispersion. In contrast, the comparative example relies solely on mechanical stirring, and the ultrafine steel fibers agglomerate severely due to their large specific surface area and electrostatic effects, which cannot meet the "uniform impact resistance" requirements of mine concrete.
[0136] In terms of early strength performance, the 1-day compressive strength of Examples 1-5 is ≥12.5MPa, and Example 1 reaches 13.2MPa, which is more than 1.5 times that of the comparative example of 8.2MPa. The key is that the soluble salt anhydrous sodium sulfate / sodium nitrate in the composite carrier of the examples releases Na⁺ after dissolving, which accelerates the hydration reaction of cement C3S and is suitable for the "rapid forming support" requirements in the low temperature environment of 10-15℃ in mines. The comparative example has no early strength component, and the hydration is slow at low temperature. The 1-day strength can only meet 50% of the surface construction and cannot be adapted to the emergency support scenario in mines.
[0137] In terms of durability and safety, Examples 1-5 exhibited a 28-day strength retention rate ≥95.2%, an annual steel fiber corrosion rate <2%, and an impact ignition temperature ≤200℃, all meeting the GB50209-2010 mine safety standard. This is attributed to the dual effect of the porous carbon matrix's porosity of 65%–70%: on the one hand, it achieves internal curing through microporous water storage, avoiding the difficulties of underground water spraying curing and ensuring stable strength; on the other hand, it adsorbs calcium hydroxide produced by cement hydration, reducing the pH value of the concrete liquid phase to 12.7–12.9, inhibiting steel fiber corrosion, while its inert structure can absorb 15%–20% of impact energy, enhancing its non-sparking performance. In contrast, the comparative example had a 28-day strength retention rate of only 82.3%, a steel fiber corrosion rate of 5.6%, and an impact ignition temperature of 260℃, posing a safety hazard.
[0138] In terms of scenario adaptability, Examples 1-5 utilize the existing compressed air system of the mine (0.4-0.6MPa) and underground water flow throughout the process, without the need for additional power supply or large equipment, and can pass through narrow underground roadways with a width of ≥0.8m; the comparative examples require external mixing equipment and a water spraying system, which is difficult to access and has high energy consumption, and does not meet the construction restrictions of "narrow space and high safety requirements" in underground mines.
[0139] In summary, Examples 1-5, through the combination of core technologies, comprehensively solve the pain points of the comparative examples in terms of dispersion, early strength, durability, safety, and scenario adaptability. The performance indicators all meet the requirements, fully verifying the necessity and inventiveness of the technical solution of the present invention.
[0140] The above embodiments can be implemented in whole or in part by software, hardware, firmware or other arbitrary combinations. When implemented by software, the above embodiments can be implemented in whole or in part in the form of a computer program product.
[0141] Those skilled in the art will recognize that the modules and algorithm steps of the various examples described in conjunction with the embodiments disclosed herein can be implemented in electronic hardware or a combination of computer software and electronic hardware. Whether these functions are implemented in hardware or software depends on the specific application and design constraints of the technical solution. Those skilled in the art can use different methods to implement the described functions for each specific application, but such implementation should not be considered beyond the scope of this application.
[0142] In addition, the functional modules in the various embodiments of this application can be integrated into one processing module, or each module can exist physically separately, or two or more modules can be integrated into one module.
[0143] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of protection of the claims.
[0144] In conclusion, the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for constructing non-sparking concrete prepared by steel fiber dispersion, characterized in that, Includes the following steps: S1: Ground prefabrication of integrated composite carrier involves mixing corn stalk ash, soluble salt, and ultrafine steel fibers in a specific ratio suitable for the non-sparking properties of concrete, the dispersion effect of ultrafine steel fibers, and the requirements for low-temperature early strength in underground mining. The mixture is then kneaded, carbonized in an inert atmosphere, crushed, and sieved to obtain a spherical integrated composite carrier. The soluble salt acts as both a pore-forming agent and an early strength reserve during the carbonization process. The carbonized corn stalk ash forms a porous carbon matrix, and the ultrafine steel fibers are fixed by being encapsulated in the porous carbon matrix and anchored by soluble salt crystals. The mass ratio of corn stalk ash to soluble salt is 3:1, and the amount of ultrafine steel fiber added is 20% of the total mass of corn stalk ash and soluble salt; the diameter of the ultrafine steel fiber is 0.08-0.12 mm and the length is 2-3 mm; the soluble salt is anhydrous sodium sulfate. S2: Underground dispersion and mixing. The integrated composite carrier obtained in step S1 is added to the hopper of the mine concrete spraying machine at a ratio of 0.8% to 1.5% of the concrete volume. Relying on the airflow provided by the existing compressed air system in the mine, the carrier is driven into a one-stop dispersion device installed on the feed pipe of the spraying machine. The carrier crushing, fiber stretching and peeling, fiber static elimination and closed-loop control of fiber concentration are completed in sequence. Then it is mixed and stirred with dry concrete and underground water to achieve simultaneous dissolution of soluble salts and uniform dispersion of ultrafine steel fibers. S3: Underground pouring and curing. The steel fiber dispersed concrete obtained in step S2 is applied to the surface of the mine roadway or chamber using a wet spraying process to form a spray layer with a thickness of 50-100mm. Internal curing is achieved through the water retention effect of the porous carbon matrix. Construction is completed after curing for 28 days. The one-stop dispersion device is a series three-level functional compartment structure. Each compartment is sealed and connected by an airflow channel. Along the airflow direction, it consists of a first-level crushing compartment for crushing the carrier, a second-level stretching compartment for stripping steel fibers, and a third-level regulating compartment for regulating fiber concentration. The entire process relies solely on mine compressed air for power and has no additional external power source. Through the above steps, the dispersion variation coefficient of ultrafine steel fibers in concrete is ≤10%, and the impact ignition temperature of concrete is ≤220℃, meeting the environmental protection and safety construction requirements of underground mines.
2. The construction method for non-sparking concrete prepared by steel fiber dispersion as described in claim 1, characterized in that, The specific prefabrication process in step S1 is as follows: S11: Corn stalk ash, anhydrous sodium sulfate, and ultrafine steel fiber are put into a twin-screw mixer and mixed for 5 minutes at 80°C and 300 r / min to obtain a mixture. S12: The mixture is fed into a carbonization furnace, N2 protective gas is introduced, and the temperature is raised to 800℃ at a heating rate of 5℃ / min. The temperature is held for 2 hours for carbonization treatment, and after natural cooling, blocky carbonized material is obtained. S13: The blocky carbonized material is crushed and screened by jaw crusher to obtain a spherical integrated composite carrier with a particle size of 8-10mm and a compressive strength of ≥3MPa. After being sealed and packaged, it is transported to the underground silo for storage.
3. The construction method for non-sparking concrete prepared by steel fiber dispersion as described in claim 1, characterized in that, In step S2, the compressed air pressure of the mine compressed air system is 0.4-0.6 MPa; the integrated composite carrier is added to the spraying machine hopper at a rate of 1.2% of the concrete volume.
4. The construction method for non-sparking concrete prepared by steel fiber dispersion as described in claim 1, characterized in that, The one-stop dispersion device is equipped with a supersonic nozzle in the primary crushing chamber. The outlet velocity of the supersonic nozzle is 350-400 m / s, which is used to crush the spherical integrated composite carrier into particles of 5-8 mm. The secondary stretching chamber is a tapered flow channel structure with an inlet diameter of 120 mm and an outlet diameter of 60 mm. The outlet velocity of the airflow after acceleration through the flow channel is 18-22 m / s, which is used to stretch and peel the ultrafine steel fibers from the carrier particles.
5. The construction method for non-sparking concrete prepared by steel fiber dispersion as described in claim 1, characterized in that, The three-stage control chamber of the one-stop dispersion device integrates an ion bar and a laser density sensor. The ion bar has a wind speed of 4-5 m / s and is used to reduce the electrostatic voltage on the surface of the ultrafine steel fiber from 5000V to ≤80V. The laser density sensor has a monitoring accuracy of ±2%. When the fiber concentration fluctuation is detected to be >5%, the opening of the compressed air valve is automatically adjusted. Through the adjustment logic that every 10% increase or decrease in the opening of the compressed air valve corresponds to a synchronous increase or decrease of 0.02MPa in the compressed air pressure, the compressed air pressure fluctuation is controlled within the range of ±0.05MPa.
6. The construction method for non-sparking concrete prepared by steel fiber dispersion as described in claim 1, characterized in that, In step S2, 5% antifreeze is added to the dry concrete mix; the amount of water added from the well is sufficient to achieve a water-cement ratio of 0.45; the mixing time is 3-4 minutes, during which anhydrous sodium sulfate completely dissolves and releases Na. + Ions promote cement hydration.
7. The construction method for non-sparking concrete prepared by steel fiber dispersion as described in claim 1, characterized in that, In step S3, the spraying pressure of the wet spraying process is 0.3-0.4 MPa; the thickness of the sprayed layer is 50-80 mm, which is suitable for the construction requirements of thin sprayed layers in underground mines.
8. The construction method for non-sparking concrete prepared by steel fiber dispersion as described in claim 1, characterized in that, The curing process in step S3 is as follows: after the sprayed layer is formed, cover it with an insulation blanket to ensure that the curing environment temperature is ≥5℃. Internal curing is achieved by utilizing the microporous water storage function of the porous carbon matrix in the integrated composite carrier. The curing age is 28 days. The porosity of the porous carbon matrix is 65% to 70%, and the surface contains 20% carboxyl and phenolic hydroxyl functional groups, which can adsorb calcium hydroxide produced by cement hydration and reduce the pH value of the concrete liquid phase to 12.7-12.
9.
9. The construction method for non-sparking concrete prepared by steel fiber dispersion as described in claim 1, characterized in that, After construction, the dispersion variation coefficient of ultrafine steel fibers in concrete is ≤6%, which is achieved by the synergistic effect of airflow stretching and electrostatic elimination of the one-stop dispersion device; the 1-day compressive strength of concrete is ≥12.5MPa, which is achieved by the release of Na from anhydrous sodium sulfate. + Ions accelerate cement hydration; 28-day strength retention rate ≥95%, this strength stability is achieved by the internal curing function of the porous carbon matrix; impact ignition temperature ≤200℃, this impact ignition performance is achieved by the inert structure of porous carbon absorbing impact energy; annual corrosion rate of ultrafine steel fibers <2%, this corrosion effect is achieved by porous carbon adsorbing calcium hydroxide to reduce the pH value of concrete liquid phase to 12.7-12.9.
Citation Information
Patent Citations
Anti-static non-ignition wear-resisting floor material and its construction method
CN101070235A
High-strength recycled aggregate concrete and preparation method thereof
CN116750997A